Role of cementoplasty in the management of compression vertebral body fractures. Issue 1004 (15th June 2009) - Hamady, M; Sheard, S
Abstract : Osteoporotic vertebral compression fractures cause pain, reduced mobility and consequently poor quality of life, and as such have a significant impact on health resources. Their prevalence can be expected to increase with the ageing population. Until recently, only conservative management has been available to alleviate pain and improve mobility. Originally developed in the 1980s to treat vascular malformation in the spine, vertebroplasty offers an interventional method for improving symptoms of vertebral compression fractures. Percutaneous vertebroplasty involves stabilisation of the fractured vertebral body using cement which is introduced via a needle under image guidance. Kyphoplasty is a more recent development in which a balloon is inflated within the fractured vertebral body in order to correct any loss of height before cement stabilisation. There is a lack of major randomised controlled trials on either procedure at present, but evidence of their safety and efficacy is increasing, suggesting that both are more effective than conservative management, with low risk of complications.